2019
DOI: 10.3390/ma12060843
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Performances of Cobalt-Doped Li2MoO3 Cathode Materials

Abstract: Co-doped Li2MoO3 was successfully synthesized via a solid phase method. The impacts of Co-doping on Li2MoO3 have been analyzed by X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction (XRD), scanning electron microscope (SEM), and Fourier transform infrared spectroscopy (FTIR) measurements. The results show that an appropriate amount of Co ions can be introduced into the Li2MoO3 lattices, and they can reduce the particle sizes of the cathode materials. Electrochemical tests reveal that Co-doping can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The decrease in average crystallite size was attributed to particle growth restriction due to the lattice distorting effects of partial replacement of Mn 4+ (0.67 Å) with Eu 3+ (10.87 Å) and has been previously observed by other authors [48].…”
Section: Crystallographic Characterizationsupporting
confidence: 75%
See 1 more Smart Citation
“…The decrease in average crystallite size was attributed to particle growth restriction due to the lattice distorting effects of partial replacement of Mn 4+ (0.67 Å) with Eu 3+ (10.87 Å) and has been previously observed by other authors [48].…”
Section: Crystallographic Characterizationsupporting
confidence: 75%
“…However, Li 2 Mn 0.95 Eu 0.05 O 3 shows a higher-level of particle size uniformity, shape uniformity and a decrease in the size of the secondary particles when compared to Li 2 MnO 3 . This has been observed in numerous reports [30,44,45,48] on doped cathode materials, and has been linked to improved porosity which could lead to enhanced performance of cathode materials due to increased surface area and shorter Li + diffusion pathways. EDX was used to determine the elemental composition of the synthesized nanostructured materials.…”
Section: Morphological Characterizationmentioning
confidence: 78%
“…At the same current density, the discharge capacity of the LMO sample after 100 cycles was only 76.5 mA h g −1 , and the capacity retention rate was only 30.5%. According to previous literature, [13][14][15][16][17][18]25,47,48 it is found that the cycling performance of pristine LMO is actually rather poor, and the reasons for this phenomenon are very complex. For Li-rich cathode materials, the irreversible phase transformation/structural rearrangement, the dissolution of the TM ions into the electrolyte, and the surface side reactions were proposed to be…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…24 In addition, it has been reported that Co doping can optimize the morphology of Li 2 MoO 3 and reduce its particle size, while K doping can stabilize the Li 2 MoO 3 structure and inhibit the phase transformation. 25,26 On the other hand, recent studies have shown that Li 2 RuO 3 , as a model compound, will lead to a higher conductivity, because its 4d orbital overlaps with the 2p orbital of oxygen, which is also responsible for the reversible anion oxidation activity of the material. 27,28 Therefore, the Ru ion has been introduced into various materials systems as a dopant, which has greatly improved the electrochemical performances of Li 4 Ti 4.95 Ru 0.05 O 12 , 29 LiNi 0.5 Mn 0.45 Ru 0.05 O 2 , 30 and LiFe 0.99 Ru 0.01 PO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Other than manganese-based, Li-rich molybdenum-based layered oxides was also attractive. Yu et al [5] investigated Co doping in Li 2 MoO 3 to improve its structure stability and electronic conductivity. Their results showed that an appropriate amount of Co ions can be introduced into the Li 2 MoO 3 lattices and electrochemical tests revealed that Co-doping can significantly improve the electrochemical performances of the Li 2 MoO 3 materials.…”
mentioning
confidence: 99%